2017
DOI: 10.1089/thy.2016.0285
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle M-Phase Genes Are Highly Upregulated in Anaplastic Thyroid Carcinoma

Abstract: Background: Anaplastic thyroid carcinoma (ATC) accounts for only 3% of thyroid cancers, yet strikingly, it accounts for almost 40% of thyroid cancer deaths. Currently, no effective therapies exist. In an effort to identify ATC-specific therapeutic targets, we analyzed global gene expression data from multiple studies to identify ATC-specific dysregulated genes. Methods: The National Center for Biotechnology Information Gene Expression Omnibus database was searched for high-throughput gene expression microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 49 publications
3
43
0
Order By: Relevance
“…Furthermore, we found relatively low expression of TSHR and SLC26A7, encoding the thyroid-stimulating hormone receptor and an iodine receptor highly expressed in normal thyroid, respectively, as well as aberrant DNA methylation in their gene bodies (Table S12). Both of these genes have been previously reported to display low expression in ATC, and aberrant methylation has previously been reported for TSHR [5,18]. However, a link between expression and methylation has not been previously reported in primary ATC.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, we found relatively low expression of TSHR and SLC26A7, encoding the thyroid-stimulating hormone receptor and an iodine receptor highly expressed in normal thyroid, respectively, as well as aberrant DNA methylation in their gene bodies (Table S12). Both of these genes have been previously reported to display low expression in ATC, and aberrant methylation has previously been reported for TSHR [5,18]. However, a link between expression and methylation has not been previously reported in primary ATC.…”
Section: Discussionmentioning
confidence: 94%
“…Gene expression analyses using microarrays have shown upregulation of genes involved in mitotic cell cycle, epithelial to mesenchymal transition, and TGF-beta signaling in ATC compared with papillary thyroid cancer (PTC) and/or normal thyroid tissue. In contrast, genes related to thyroid hormone synthesis and differentiation have been reported to be downregulated [4][5][6][7][8][9]. However, all expression studies published so far were conducted on small cohorts, including ≤20 cases.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ANLN may be a useful prognostic indicator and an important therapeutic target in the treatment of pancreatic cancer. Previous studies have shown that ANLN is upregulated in many cancers and may serve as a promising prognostic biomarker for cancer [13][14][15][16][17][18]. For example, ANLN was upregulated in bladder urothelial carcinoma, and elevated ANLN expression was correlated with poor progression-free and recurrence-free survival [16].…”
Section: Discussionmentioning
confidence: 99%
“…In normal tissues, ANLN expression is higher in the placenta, brain and testis, and lower in the lung, heart, liver and spleen [8]. Many recent studies suggests that ANLN is upregulated in numerous cancer types, including cervical cancer, prostate cancer, anaplastic thyroid carcinoma, breast cancer, lung carcinogenesis, bladder urothelial carcinoma, pancreatic cancer and nasopharyngeal carcinoma [9][10][11][12][13][14][15][16]. Functionally, increasing evidence has indicated that ANLN is critical for growth and metastasis of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The biggest example is the recent deal between a very famous application company called Snapchat and Google to rent the entire application development infrastructure through the Google Cloud Platform (GCP) service [5] [6] [7]. Other than that, various reputable organizations and financial institutions are expected to be multi-billion markets for the cloud computing industry [8].…”
Section: Chapter 1: Introductionmentioning
confidence: 99%